Genghis Khan and the Mongol Empire - Nardo, Don 1947-; Gale Group (Detroit, Michigan Lucent Books, 2010)
Provides an overview of important historical events or periods in world history. This volume focuses on Temujin, the future Genghis Khan, and the Mongol Empire.
Important dates at the time of the Mongol Empire -- Introduction : from barbarian to modern man -- Ancient peoples of the steppes -- The rise of Genghis Khan -- Military and legal reforms -- Subduing Northern China -- Conquests in Western Asia -- The Mongols after Genghis Khan -- Glossary.
Description based on print version record.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Genghis Khan -- 1162-1227.; Mongols -- Kings and rulers -- Biography; Mongols -- History; Electronic books